PEMBINAAN MASYARAKAT SEBAGAI APLIKASI GERAKAN MASYARAKAT CERDAS MENGGUNAKAN OBAT (GEMA CERMAT) PADA SISWA MTS WIHDATUL ULUM DESA BORISALLO KABUPATEN GOWA. - Azizah, Rizqi Nur (Jurnal BALIRESO, 2020)
Gerakan Masyarakat Cerdas Menggunakan Obat "GeMa CerMat" is an effort of the governmentand society through a series of activities in realizing community care, awareness, understandingand skills in using drugs correctly and correctly. UMI as an education and da'wah institutionalways supports government programs in the health sector. The target of this service is thestudents of MTs Wihdatul Ulum Desa Borisallo, Parangloe Subdistrict, Gowa Regency, who areable to get to know things related to drugs and can use drugs safely and avoid the effects ofunwanted drugs. In addition, it is expected to be able to inform drug related matters to othercommunities. The method of disseminating service activities to the Wihdatul Ulum Islamicboarding school, counseling on rational use of medicine with lecture and discussion methods, thencontinued with training in rational drug use through Active Learning Method (CBIA) methods,evaluation of service activities, and publication of activities in the media print and online. Fromcounseling activities and rational drug use training conducted to MTs students. Wihdatul UlumDesa Borisallo Kec. Parangloe Gowa Regency, which was attended by 30 participants, obtained anaverage pretest value of 0.3 and an average posttest value of 4.8. The Efforts of the SmartCommunity Movement to Use Medication (GeMa CerMat) for Students of MTs Wihdatul Ulum inBorisallo Village, Gowa Regency effectively increase knowledge related to drugs in selfmedication.